The efficacy of incorporating Artificial Intelligence (AI) chatbots in brief gratitude and self-affirmation interventions: Evidence from two exploratory experiments - Jing Wen Hung; Andree Hartanto; Adalia Y.H. Goh; Zoey K.Y. Eun; K.T.A. Sandeeshwara Kasturiratna; Zhi Xuan Lee; Nadyanna M. Majeed (Computers in Human Behavior: Artificial Humans)
Numerous studies have demonstrated that positive psychology interventions, including brief interventions, can significantly improve well-being outcomes. These findings are particularly important given that many of these interventions are brief and self-administered, making them both accessible and scalable for large populations. However, the efficacy of positive psychology interventions is often constrained by small effect sizes. In light of advancements in generative Artificial Intelligence (AI), this study explored whether integrating AI chatbots into positive psychology interventions could enhance their efficacy compared to traditional self-administered approaches. Study 1 examined the efficacy of a gratitude intervention delivered through Snapchat's My AI, while Study 2 evaluated a self-affirmation intervention integrated with a customized ChatGPT. Both studies employed within-subject experimental designs. Contrary to our hypotheses, the integration of AI did not yield incremental improvements in gratitude outcomes (Study 1), or self-view outcomes (Study 2) compared to existing non-AI interventions. However, exploratory analyses revealed that the AI-integrated self-affirmation intervention significantly enhanced life satisfaction and medium-arousal positive affect, suggesting potential benefits for selected well-being outcomes. These findings indicate that while AI integration in brief, self-administered positive psychology interventions may enhance certain outcomes, its suitability varies across intervention types. Further research is needed to better understand the contexts in which AI can effectively augment positive psychology interventions.